Degradabilidade ruminal da matéria seca e da fração protéica da silagem de milho, do farelo de soja e do sorgo grão, em bovinos da raça nelore. Comparação com os dados obtidos pelo CNCPS - Rossi Júnior, Paulo; Silva, Aliomar Gabriel da; Wanderley, Ruy da Carvalheira; Vieira Bose, Máx Lázaro; Boin, Celso (My University, 1997)
The nylon bag in situ degradation thecnique was employed to compare the data of the CNCPS to the ruminal degradability of the dry matter and crude protein in corn silage, soybean meal and sorghum grain, in four rumen fistulated Nellore steers, averaging 36 months of age and 520 kg of liveweight. A randomized complete block experimental design was used, where animals constituted the blocks. Two levels of concentrate, 18 and 39 %, were used in the diets. The forage used in the diets was corn silage and the concentrate ingredients were: soybean meal, cottonseed meal, corn grain and sorghum grain. There was a reduction in the potentially by degradable fraction (B) of the dry matter(DM) of the corn silage and sorghum grain with an increase in the concentrate level of the diet; however, the degradation rate(c) of the silage was similar for the two diets and the sorghum grain showed an increase of 28.4 %. The B fraction of the DM from the soybean meal was not affected by the diet, but its rate (c) was reduced by 18.1 %. The same effect was observed for the rate(c) of crude protein(CP) of the soybean meal, with a reduction of 38.1 %. The values for the effective degradability of the two fractions were not affected by the diet when the lag time was not considered. When lag time was considered, the degradability values of the studied feeds were superior in both fractions.
Ruminal degradability of the dry matter and crude protein of the corn silage, soybean meal and sorghum grain in nellore cattle. Comparison with data of the CNCPS
Keywords: Corn silage; Crude protein; Dry matter; Nellore; Ruminal degradability; Sorghum grain; Soybean meal; Technique in situ; Animalia; Bos taurus; Glycine max; Micropus; Zea mays